2013
DOI: 10.1371/journal.pone.0079510
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Randomised Placebo-Controlled Treatment Trials for Depression and Anxiety in Parkinson’s Disease

Abstract: BackgroundPsychopharmacotherapy currently constitutes the first-line treatment for depression and anxiety in Parkinson’s disease (PD) however the efficacy of antidepressant treatments in PD is unclear. Several alternative treatments have been suggested as potentially more viable alternatives including dopamine agonists, repetitive transcranial magnetic stimulation, and cognitive behavioural therapy (CBT).MethodA meta-analysis of randomised placebo-controlled trials for depression and/or anxiety in PD was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 69 publications
(79 reference statements)
2
92
0
4
Order By: Relevance
“…The most frequently prescribed type of antidepressant, SSRIs, is comparable to past American Veteran Affairs studies involving patients with Parkinson disease and depression. 14,15 In addition, depression treatment in the general population shows a high prescribing average (68.0%) of SSRIs in Canadian primary care practices. 18 Possible explanations for this high frequency might be the current general prescription trends and lower adverse effect profile compared with other antidepressants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently prescribed type of antidepressant, SSRIs, is comparable to past American Veteran Affairs studies involving patients with Parkinson disease and depression. 14,15 In addition, depression treatment in the general population shows a high prescribing average (68.0%) of SSRIs in Canadian primary care practices. 18 Possible explanations for this high frequency might be the current general prescription trends and lower adverse effect profile compared with other antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous work using American Veteran Affairs data examined simultaneous treatment of Parkinson disease and depression. 14,15 Yet, there remains limited knowledge as to how these 2 chronic conditions are treated in Canadian primary care or the patient characteristics of those with both Parkinson disease and depression.…”
mentioning
confidence: 99%
“…These results were generally consistent with two other recent meta-analyses of pharmacological treatment of depression in PD, suggesting superiority of TCAs to SSRIs in reducing PD depression symptoms. 61,62 In contrast to Troeung et al's 60 findings, Bomasang-Layno et al 59 did not find a significant effect of TCAs in the treatment of depression in PD but found that when stratifying SSRI/SNRI treatments versus other pharmacological treatments, the SSRI/SNRI treatment studies showed a significant effect on depressive symptoms in PD. Of note, Troeung et al 60 also caution that the nonsignificant treatment effect in SSRIs may be due to the limited number of randomized controlled trials (RCTs) included for analysis (N=5) and highlighted the need for additional, carefully designed studies.…”
Section: Treatment Pharmacological Managementmentioning
confidence: 87%
“…Indeed, several small, controlled trials using selective serotonin reuptake inhibitors (SSRIs) failed to show efficacy in PD depression, although a recent meta-analysis showed significant effect of antidepressant treatment on depressive symptoms in PD when SSRI and serotonin-norepinephrine reuptake inhibitors (SNRI) treatment studies were combined. [57][58][59] Troeung et al 60 recently published a meta-analysis of randomized, placebo-controlled trials for the treatment of anxiety and depression in PD. Of note, this analysis was limited to PD patients who met DSM criteria for depressive or anxiety disorder.…”
Section: Treatment Pharmacological Managementmentioning
confidence: 99%
See 1 more Smart Citation